Jornalismo gonzo e parresía : mentiras sinceras e outras verdades - Ritter, Eduardo (2015)
In the early 1980s, the French philosopher Michel Foucault, teaching courses at the Collège de France, addressed the history and the concept of parresia, a Greek word. Briefly, the term means to speak frankly in public space taking risks by such this attitude. From this idea, this thesis works with the application of this concept in the journalistic field, with the object of study being the gonzo journalism, practiced by US journalist Hunter Thompson (1937-2005). In addition, the thesis presents a critique about the journalism practiced throughout history in the Western world, precisely because it presents ideologically a search for the truth of the facts, while in practice it doesn‟t happen. Faced with such complexity, speech frank journalism becomes a major alternative for those journalists who seeking to practice a journalism that tries to be minimally committed to the truth. Ironically, sometimes the fiction and the literature technics that enable the author to tell the truth, thus creating a complex relationship between Philosophy, Literature and Journalism. It is at this intersection that is what I call journalistic parresia and gonzo journalism - which makes use of the courage of truth, but without giving up sincere lies.